PENANAMAN PENDIDIKAN KARAKTER PEDULI LINGKUNGAN DI SEKOLAH DASAR - Arifin Muslim; Novica Dimar Azizah; Supriatna Supriatna; Eneng Dian Nurwulan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This research was conducted based on the indicators of character education on environmental care which aimed to find out and analyze the school curriculum, the applying process of character education during learning in the class, the implementation, supporting factors, and hampering factors in implementing character education on environmental care. This was a descriptive qualitative research which focused on the indicators that must be achieved by the school and students. The main sources of this research were the school principal, the teachers and students of second and fifth grades. The data were collected using observation, interview, and documentation with the researcher himself as the instrument. The data were then analyzed using data reduction, data display, and conclusion. The data validity in this research used triangulation technique which was source triangulation. The results showed that the implementation of character education on environmental care was done based on the school curriculum in regular activities, spontaneous activity, exemplary, and conditioning; the applying process of character education during learning in the class and at school; the implementation of character education could be seen from eight indicators which had been achieved by the school, six indicators which had been done by low and high-class students. The supporting factors were also found at school in the form of infrastructure and the role of school environment. However, there were also hampering factors such as time issue which caused less maximal implementation and the lack of giving reward to the students who had cared with environment.